A splicing enhancer exhibits both constitutive and regulated activities. - Ming Tian; Tom Maniatis (1994)
The Drosophila proteins Transformer (Tra) and Transformer2 (Tra2) regulate the sex-specific alternative splicing of Drosophila doublesex (dsx) pre-mRNA by specifically binding to a splicing enhancer (dsx repeat element; dsxRE) located 300 nucleotides (nt) downstream from a female-specific 3' splice site. In this paper we show that the dsxRE can function as a Tra and Tra2-independent splicing enhancer in vitro when located within 150 nucleotides of the 3' splice site. Based on the relative levels of SR proteins that bind stably to the dsxRE in the presence or absence of Tra and Tra2, we propose that the constitutive splicing activity of the dsxRE is mediated by its weak interactions with SR proteins and possibly other general splicing factors. In contrast, Tra and Tra2 allow the dsxRE to function at a distance from the intron by stabilizing the interactions between these proteins and the dsxRE.